Pendampingan Refleksi Sekolah Penggerak Jenjang Sekolah Dasar di Kabupaten Gresik - Achmad Rijanto; Suesthi Rahayuningsih (CV. Multi Kreasi Media, 2023)
One of the driving school assistance programs was carrying out reflection activities on educational units. Reflection activities were held every 3 months. The purpose of this activity was that it was hoped that the driving school will be able to identify the achievements of the implementation of the Merdeka curriculum as a reference for preparing work plans every 3 months in the future. The partner for this community service activity was the UPT SD Negeri 25 Gresik driving school. The problem faced by partners in this reflection activity was that there was still a lack of knowledge about identifying the achievements of the implementation of the Merdeka curriculum including school conditions, good practices, challenges and strategies, educational unit actors that can be involved, and realistic follow-up plans related to the implementation of the independent curriculum. The method used was to use the mentoring method, by carrying out activities in the form of reflection on activities online once every 3 months. The results achieved from this community service activity are worksheet documents as a result of reflection on the implementation of the Merdeka curriculum, including identification of school conditions related to the implementation of the Merdeka curriculum, identification of things that were going well and things that were still a challenge, input and recommendations for stakeholders and follow-up plans realistic according to the results of reflection.